Empirical Evidence Of Bullying Effect On Gender Perspective In South Sulawesi - Syahruddin Mahmud; Rosmawati Abdul Maing (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
Bullying in school In Indonesia has commenced to receive serious attention. Explanation about gender and bullying effect have been offered by many scholars. This recent research has focused on gender differences in bullying effect such as depression and anxiety. It is drawing on quantitative methodological study of bullying effect at 536 students at high school in South Sulawesi Indonesia. It is identified that statistically, bullying effect such as anxiety and depression in Indonesia are significantly different between male and female.  Anxiety and depression are the potential effect of bullying. The result documented that there is a significant difference between depression effects of bullying towards gender. Similarly, It is identified to anxiety effect that there is also a significant difference between anxiety effects towards gender. Bullying effects are significantly different in term of gender in South Sulawesi Province, Indonesia.